Understanding Low Earth Orbit (LEO) Satellites and Policy Issues - York, Dan (Global Governance of Low Earth Orbit Satellites, 2025)
Abstrakt:Low Earth Orbit (LEO) satellite systems like Starlink and OneWeb are transforming global internet access by reducing latency and expanding coverage. This chapter explains the basics of satellite internet, comparing traditional geostationary orbit (GEO) systems—where satellites remain fixed over the Earth—with LEO satellites that orbit closer to the surface, enabling faster connections. It outlines key components including satellites, user terminals, and ground stations, and discusses regulatory challenges such as spectrum allocation, consumer equipment approval, and landing rights, all governed by national authorities and the International Telecommunication Union (ITU). The chapter highlights the critical policy intersections raised by LEO deployments, emphasizing the need for coordinated international governance to address issues of access, security, and equitable connectivity.